Chanakya on management - GARDE (Ashok R) (Ahmedabad Jaico Publishing House, 2010)
Canakya's Arthasastra deals with the different aspects of managing a kingdom, including management of men. The principles contained in Canakya's work have the unique distinction of being used successfully in practice to achieve good results on a sustainable basis. The management principles used in the USA or in Japan are derived from their own cultural background. There exists enough evidence to show that these systems, even when meticulously and earnestly adopted in India, rarely take roots or produce the desired results. We need to look for those principles that make sense in our own social and work culture and which would hopefully deliver better results for all concerned - the customers, the investors, the employees and the society. This book on the management philosophy and practice of Canakya is the author's earnest attempt to help Indian readership to become familiar with the great work of the First Total Management Guru of the world.
Keywords: on; management; Chanakya